FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN ALAT KONTRASEPSI - Dita Wasthu Prasida (LPPM Institut Pendidikan Nusantara Global, 2023)
Family Planning (KB) is a program established by the National Population and Family Planning Agency (BKKBN) which aims to control the population in Indonesia. In implementing the family planning program, this is done by using contraceptives. The word contraception comes from the word